A non-exothermic cell-embedding tissue-mimicking material for studies of ultrasound-induced hyperthermia and drug release. - Mylonopoulou, E; Bazán-Peregrino, M; Arvanitis, C; Coussios, C (2013)
PURPOSE: The present study aims to create and characterise a cell-embedding tissue-mimicking material (TMM) that has thermal and acoustic properties similar to liver tissue, in order to enable study and optimisation of protocols for ultrasound-induced hyperthermia and drug delivery. MATERIALS AND METHODS: An agarose-based, cell-embedding TMM was iteratively developed and characterised. The acoustic properties (attenuation coefficient, speed of sound and cavitation threshold) and thermal response of the material were compared with those of fresh degassed liver tissue over a range of acoustic pressures and frequencies. A luminescence intensity assay was used to evaluate viability of HuH-7 cells in the material. The efficacy of ultrasound-mediated chemotherapeutic treatment in the material was tested by localised activation of low temperature thermally sensitive liposomes. Drug activation was measured by fluorescence microscopy. RESULTS: Similar acoustic properties (attenuation coefficient, speed of sound) to liver tissue were achieved over the therapeutically relevant frequency range of 1-4 MHz and similar thermal response was achieved for acoustic pressures up to 4.8 MPa peak to peak (ppk) at 1.1 MHz. Above 4.8 MPa ppk cavitation enhanced heating occurred in the TMM. Drug release from low-temperature-sensitive liposomes was achieved with 4.4 MPa ppk 6-s exposures at 1.1 MHz and cell compatibility of the material was confirmed. CONCLUSIONS: A platform for in vitro work for activation of thermally sensitive liposomes using high intensity focused ultrasound (HIFU)-induced hyperthermia was established. The TMM presents similar acoustic properties and thermal response to liver tissue over a broad range of ultrasound exposure conditions.